Effects of Earth–Rock Dam Heterogeneity on Seismic Wavefield Characteristics - Hao Xu; Xinjiang Yu; Fei Cheng; Yuxi Ma; Jialiang Li; Xiaohuan Jiang (Energies, 2023)
Earth–rock dams are typical soil–rock mixtures with high heterogeneity. Mastering the effect of dam heterogeneity on seismic wavefields is the premise of accurately detecting hidden risks in dams. In this paper, based on the soil–rock mixture characteristics of actual dams, a soil–rock mixture model that can reflect the heterogeneity of dams is established through local segmentation and reassignment of random disturbances. The influence of local area size on model heterogeneity is described. The seismic wavefield in a soil–rock mixture dam is numerically simulated through a staggered-grid finite-difference algorithm with second-order accuracy in time and sixth-order accuracy in space. Then, the effect of dam heterogeneity on effective wavefields is analyzed. The results show that the heterogeneity of the earth–rock dam can lead to scattered waves in the seismic wavefield, and the scattered waves are mainly generated by Rayleigh surface waves. In the seismic record, scattered waves with strong energy appear in the region below the surface waves. The scattered wave energy is weak and close to that in the homogeneous media in the region above the surface waves. As the rock content in the dam increases, the scattering of seismic wavefields and the energy of scattered waves weaken gradually. The scattered waves generated by the heterogeneity of the dam significantly impact the reflected longitudinal wave and converted wave but, affect the reflected shear wave less. The numerical simulation results are consistent with the acquired seismic wavefield from the field test, proving the effectiveness of the numerical simulation for the seismic wavefield propagation characteristics of the earth–rock dam.